2013
DOI: 10.1002/j.2333-8504.2013.tb02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Alternative Test Form Linking Designs With Modified Equating Sample Size and Anchor Test Length

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There are many linking procedures that place both exams onto the same scale. For example, the fixed parameter with score transformation procedure, and the mean-mean or mean-sigma procedure are commonly used linking procedures [22][23][24]. For these assessments it was found that the mean-mean procedure produced the most acceptable transformation between the two scales.…”
Section: Information Functions and Scale Comparisonmentioning
confidence: 99%
“…There are many linking procedures that place both exams onto the same scale. For example, the fixed parameter with score transformation procedure, and the mean-mean or mean-sigma procedure are commonly used linking procedures [22][23][24]. For these assessments it was found that the mean-mean procedure produced the most acceptable transformation between the two scales.…”
Section: Information Functions and Scale Comparisonmentioning
confidence: 99%
“…Both the item parameter transformation and the IRT true score equating phases were accomplished using ICEDOG software (Robin, Holland, & Hemat, ). The statistics of interest in this study were the standard errors of the estimated scaling coefficients A and B in the item parameter transformation (linking) phase and the standard errors of the scale scores. The grouped jackknifing procedure was implemented to estimate the standard errors in both the linking and the equating phases (Qian, ; Wang et al, ) on the entire sample data of a test form and on each jackknife replicate sample. The jackknifed standard errors of the statistics of interest were estimated as follows.Let trueθ^ be the parameter estimated from the whole sample and θtrue^j be the estimate from the j th jackknife replicate sample.…”
Section: Methodsmentioning
confidence: 99%
“…The statistics of interest in this study were the standard errors of the estimated scaling coefficients A and B in the item parameter transformation (linking) phase and the standard errors of the scale scores. The grouped jackknifing procedure was implemented to estimate the standard errors in both the linking and the equating phases (Qian, ; Wang et al, ) on the entire sample data of a test form and on each jackknife replicate sample. The jackknifed standard errors of the statistics of interest were estimated as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lord (1975), IRT methods of equating is useful, especially in increasing the stability of the scales near the extreme values and in reducing drift in equating chains of several test forms. Wang, Qian, and Lee (2013) evaluated the combined effects of reduced equating sample size and shortened anchor test length on item response theory (IRT)-based linking and equating results. The presence of anchor items requires additional considerations because these items play a large role in determining the equating function.…”
Section: Introductionmentioning
confidence: 99%